Use of a toolbox of tailored evidence-based interventions to improve children's physical activity and cardiorespiratory fitness in primary schools: results of the ACTIPROS cluster-randomized feasibility trial - Berit Brandes; Louisa Sell; Christoph Buck; Heide Busse; Hajo Zeeb; Mirko Brandes (BMC, 2023)
Abstract Background School-based physical activity (PA) promotion is usually conducted by providing one specific intervention. In contrast, the ACTIvity PROmotion via Schools (ACTIPROS) toolbox provides a set of twelve evidence-based PA interventions serving different domains of the Health Promoting Schools framework that primary schools can select according to their requirements. In this study, we tested the feasibility of the toolbox approach in primary schools. Methods A two-arm cluster-randomized feasibility trial at primary schools (n = 5 intervention schools [IS], n = 5 control schools) located in the Federal State of Bremen, Germany, was conducted. Children's habitual PA (GENEActiv, Activinsights Ltd.) and motor skills (Deutscher Motorik Test; DMT) were measured at the beginning (t0: Sept and Oct 2021) and at the end of the school year (t1: June and July 2022). Between Oct 2021 and July 2022, the ACTIPROS toolbox was implemented at IS. Teachers documented intervention choices and implementation within a short questionnaire (SIQ) at t1. Results IS successfully implemented at least one intervention of the toolbox. In total, seven out of twelve possible interventions were selected. Two schools decided to replace an intervention with another during the trial. Results of the SIQ indicated that IS tended to choose similar interventions while implementation frequency was highly different. N = 429 students from two classes per school were recruited. The mean consent rate was 75.1% (n = 322). At t0 and t1, n = 304 (94.4%) and n = 256 (79.3%) of consented children took part in the DMT, respectively. The accelerometry sample included one class per participating school. At t0 and t1, n = 166 and n = 151 devices were handed out to students and n = 133 (80.1%) and n = 106 (70.2%) valid records could be retrieved, respectively. Linear mixed models showed an intervention effect of 15.5 min (95% CI: 4.5; 26.6) in children's daily MVPA at IS between t0 and t1 compared to controls. Conclusions All IS were able to implement at least one intervention from the toolbox, and unsuitable interventions were successfully replaced in a timely manner, highlighting the feasibility of implementing the ACTIPROS toolbox. Good consent rates for accelerometer and motor skills data were achieved. Results indicate a substantial increase in MVPA associated with the ACTIPROS toolbox and need to be tested in a larger sample. Trial registration German Clinical Trials Register DRKS00025840.